IMPLEMENTASI ALGORITMA ITERATIVE DICHOTOMOCER 3 (ID3) PADA KLASIFIKASI KELULUSAN SISWA - Siti Yuliyanti; Dedy Apriyadi; Hamdan Arsyad (LPPM STMIK BANDUNG, 2019)
Institutions of state and private must have a policy different curriculum, the education level of vocational school graduation rates with High value remains low this is caused by several factors, which include: The length of the handling of students due to the delayed decision by the school, delays in decision-making or action against the students because there is no media that can help the school in predicting graduation accurately and quickly. From some of these factors led to a lot of students who scored less than satisfactory. To overcome these problems, the authors created a solution to implement data mining, utilizing academic grades, The study used a model approach waterfall method. Wherein the process includessystem / Information Engineering,analysis, Design, coding, testing, maintenance, Collecting data using techniques such as interviews and observation. Once the data is collected and there will be continued ketahap Analysis and design using object-oriented programming approach to design using UML (unified modeling language). The support device antaralain is an activity diagram, usecase diagram, sequence diagram, component diagram, deployment diagram, and class diagram. Researchers using the database design ERD (entity relationship diagram) and Relational Database.